Study of prevalence of insulin resistance and other metabolic abnormalities in various phenotypes of polycystic ovary syndrome in central India - Gupta, Deepti; Upadhyaya, Rini; Bhati, Anjlina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Till recent times, defining symptoms of PCOS remained a debatable topic. In 2012, National Institute of health consensus panel proposed diagnostic criteria based on phenotypes. Evidence showed higher incidence of diabetes mellitus, insulin resistance and compensatory hyperinsulinemia among women with PCOS. So, the present study was undertaken to compare the clinical, metabolic and hormonal profile among various phenotypes in women with PCOS and to find out the prevalence of insulin resistance among the PCOS phenotypes. Methods: The prospective, observational study was done on 292 women with PCOS-related infertility. These women were divided into 4 phenotypes. Ferriman-Gallwey score, HOMA-IR, OGTT, lipid parameters, hormonal parameters, mean ovarian volume and mean antral follicle counts were compared among the 4 phenotypic groups. One-way ANOVA followed by post-hoc Tukey was applied. Results: Mean weight, BMI, waist circumference, SBP, DBP and Ferriman-Gallwey score, fasting glucose, fasting insulin, OGTT (1 hour) and HOMA-IR was highest in phenotype A, while fasting glucose / insulin ratio was lowest in phenotype A. Total triglycerides, total cholesterol, LDL were higher and HDL was lowest, testosterone, mean ovarian volume and mean antral follicle count were highest and vitamin D was lowest in Phenotype A. Conclusions: Phenotype A is the group with all features of PCOS syndrome, while phenotype D is associated with milder metabolic profile. Women with phenotype A and B are at a higher risk for metabolic syndrome. Identifying various phenotypes will assist in providing appropriate treatment and prognosticating the patients with PCOS-related infertility.